Analisis wacana kritis ayah yang memiliki anak dengan spektrum autisme - Yunianti, Elvi; Nanik, Nanik; Wijaya Mulya, Teguh (Jurnal Psikologi Ulayat, 2025)
Families raising children on the autism spectrum experience significant parenting challenges. To provide effective support, it is important to understand the distinct roles and experiences of fathers and mothers. Existing family research has predominantly focused on mothers as primary caregivers, leaving fathers' voices underrepresented. Consequently, support for fathers is often generalized from findings based primarily on mothers’ experiences. Using a critical discourse analysis approach, this study aims to construct a discourse that uncovers the hidden social power driving marginalization in the context of caregiving and disability, experienced by fathers. Findings from interviews with 14 fathers of children on the autism spectrum reveal three dominant discourses that shape their understanding of their roles, influenced by sociocultural dynamics. These discourses include: (1) discourse on the transformation of gender roles in the family; (2) the discourse of social power: norms, stigma, and hierarchy; and (3) cultural discourse: the construction of autism in society.